Scientific and practical approach to physical conditioning of athletes - Jukic, I.; Milanovic, D.; Markovic, G.; Milanovic, L.; Simek, S.; Gregov, C. (Serbian Journal of Sports Sciences, 2007)
Physical conditioning can be defined as the process of improvement of motoric and functional (energetic) abilities, morphological characteristics, athletes' health status and also improving the skills responsible for those aspects. The realization of physical conditioning as an important aspect of athletes' preparation caused large interest of scientists. That interest is mostly addressed to conditioning qualities of athletes (diagnostics, modelling, relationships, differences), but also to procedures for their improvement (means, methods and programs). There are several basic directions of research of physical conditioning of athletes: diagnostics and modelling of conditioning qualities, the relationships between conditioning qualities, the relationships between conditioning qualities and the success in a certain sport, the differences in conditioning qualities of athletes of different age, gender, rank and kind of sport analysis of exercises of physical conditioning of athletes, modelling and valorization of methodical procedures in physical conditioning. The improvement of conditioning practice is only possible with strong support of scientific research. It is important to ensure the flow of scientific information to sport experts - practitioners.